Crime e morte no Pernambuco oitocentista (1859-1861): o caso do assassinato de Manoel Ledo de Lima. - Torri, Nathalia Pereira (2024)
This research is about criminal proceeding that deal with murder of landowner and captives Manoel Ledo de Lima, commited in july 1859, in Villa Bella, Pernambuco, Brazil. The sources that we will use in this investigation are the laws currents in the período indicated, the nerspapers, the process of the enslaved Thomaz (used as a paradigm) and the criminal case in which the enslaved Balbino was accused. As for theory and methodology, we use the teachings of James C. Scott, Marc Bloch, Carlo Ginzburg, among others. The research intends to study the criminal process in comment. It is necessary, in the comparison of these sources, to take into account beyond what is written in them. It is also necessary to perceive the sociocultural context in which the enslaved are immersed, because, as he warns Arlette Farge, in the processes, men are not fully analyzed, but only crystallized in disturbing social facts (FARGE, 2009, p. 32). For this, research will be developed,in the inductive method, from, in addition to the sources in question, of the historiographical discussion, allowing the perception of the political nature of judicial decisions, consistent in elite readings of slavery, and also the vulnerability of some defendants by reason of their miserable state.